1r=1t-4

Rewrite the equation as 1t-4=1r.

1t-4=1r

Multiply each term by a factor of 1 that will equate all the denominators. In this case, all terms need a denominator of r(t-4). The 1t-4 expression needs to be multiplied by rr to make the denominator r(t-4). The 1r expression needs to be multiplied by t-4t-4 to make the denominator r(t-4).

1t-4⋅rr=1r⋅t-4t-4

Multiply the expression by a factor of 1 to create the least common denominator (LCD) of r(t-4).

1(r)

Multiply r by 1.

rr(t-4)=1r⋅t-4t-4

Multiply the expression by a factor of 1 to create the least common denominator (LCD) of r(t-4).

1(t-4)

Multiply t-4 by 1.

rr(t-4)=t-4r(t-4)

rr(t-4)=t-4r(t-4)

Since the expression on each side of the equation has the same denominator, the numerators must be equal.

r=t-4

Rewrite the equation as t-4=r.

t-4=r

Add 4 to both sides of the equation.

t=r+4

Solve for t 1/r=1/(t-4)